Answer

Verified

382.2k+ views

**Hint:**From the given question we have to show that one value of \[\Rightarrow \left[ \sqrt{1+iy}+\sqrt{1-iy} \right]=\sqrt{2x+8}\].Here in this problem we have manipulate and get the proof by using the basic mathematics and having a general knowledge in regarding the square roots and the complex numbers.

\[y=\sqrt{{{x}^{2}}+6x+8}\]

**Complete step-by-step solution:**

By squaring the given question on both the right hand and left hand side of the equation the equation becomes

\[\Rightarrow {{y}^{2}}={{x}^{2}}+6x+8\]

By bringing the whole terms in left hand side to right side of the equation that is the whole terms to one side we get,

\[\Rightarrow {{x}^{2}}+6x+8-{{y}^{2}}=0\]

Let in the equation we consider the y will be an constant and so after assuming it as an constant it will become a quadratic equation so by basic formula of quadratic equation the roots can be expressed as follows

\[\Rightarrow x=\dfrac{-6\pm \sqrt{36-4\left( 8-{{y}^{2}} \right)}}{2}\]

By the general arithmetic simplifications as addition and multiplication the equation becomes as follows

\[\Rightarrow x=\dfrac{-6\pm \sqrt{36-32+4{{y}^{2}}}}{2}\]

By general simplification sending the 6 to other side after multiplying the x with two the equation becomes as follows

\[\Rightarrow 2x+6=\dfrac{\pm \sqrt{36-32+4{{y}^{2}}}}{1}\]

From solving the terms or expression inside the square root the equation becomes as follows

\[\Rightarrow 2x+6=\pm 2\sqrt{1+{{y}^{2}}}\]

From adding the 2 on both the sides the equation will be as follows

\[\Rightarrow 2x+8=2+2\sqrt{1+{{y}^{2}}}\]

\[\Rightarrow 2x+8=1+iy+1-iy+2\sqrt{\left( 1+iy \right)\left( 1-iy \right)}\]

\[\Rightarrow 2x+8={{\left[ \sqrt{1+iy}+\sqrt{1-iy} \right]}^{2}}\]

**Appling the square root on both sides the equation becomes as follows and as required in the question. \[\Rightarrow \left[ \sqrt{1+iy}+\sqrt{1-iy} \right]=\sqrt{2x+8}\].**

**Note:**We must be very careful in doing calculations and must be having knowledge regarding the finding the roots of a quadratic equations and must not do mistakes or else it would end up with total misleading solution example here we use \[{{i}^{2}}=-1\]rather that this if we use \[{{i}^{2}}=1\]then we can get\[\sqrt{1+{{y}^{2}}}=\sqrt{\left( 1+iy \right)\left( 1-iy \right)}\] in our solution. So we must have good touch in complex numbers.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Difference Between Plant Cell and Animal Cell

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Change the following sentences into negative and interrogative class 10 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Select the word that is correctly spelled a Twelveth class 10 english CBSE